Prostate Cancer Leading-edge Diagnostic Procedures and Treatments - Mohan, Ravinder (IntechOpen, 2016)
Prostate cancer is diagnosed commonly in the course of general health screening. Very often it is difficult to tell whether the cancer will be aggressive and lethal or will be so slow growing that it will not affect the patient's survival. Treatment can have a major impact on the patient's health-related quality of life. This book presents cutting-edge research in predicting the behavior of localized and metastatic cancer, targeted treatment of cancer that has spread minimally, response to newer methods of treatment, and rehabilitation of patients.